REVENUE AS A MODERATING VARIABLE ON THE EFFECT OF WORKING CAPITAL CREDIT ON NET INCOME - Kiki Muli Fardian; Juita Sukraini; Nidia Anggreni Das (SEAN Institute, 2023)
This research aims to assess how Working Capital Credit affects Net Income, with Revenue acting as a moderating variable. The study considers all BUMN banks listed on the Indonesia Stock Exchange (IDX), with a sample of four banks and eight years of financial reports (2014-2021) analyzed through Moderated Regression Analysis (MRA). Results indicate that Working Capital Credit has a significant positive impact on Net Income, while Revenue plays a moderating role in the relationship between the two. The findings suggest that firms must consider the impact of sales as a moderating variable to optimize working capital credit utilization and increase net income.